Selection and Phenotypic Stability of M4 Mutants of Pearl Millet (Pennisetum glaucum (L.) R. Br.) Derived from Gamma Rays Induced Mutagenesis - Boureima, Mouhamadou Mounkaila; Ousmane, Sani Daouda; Yacouba, Abdoul-Bachir Issa; Daoud, Abdoul Razak Sani; Adamou, Nassirou Mahamadou; Lawali, Mamane Nassourou; Sounakoye, Illiassa Soumaila (European Scientific Journal, ESJ, 2024)
Gamma irradiation mutagenesis is an approach that offers a wide range of possibilities for varietal selection. It consists of simultaneously inducing multiple mutations to modify several plant traits. The aim of the present study was to select seed lots for four mutants in the M4 generation. An experiment was carried out in an experimental plot to purify drought-tolerant M4 genotypes based on morphological characteristics. Potential mutants MI 02/82, MI 13/63, MI 12/72 and MI 10/54 were tested in a randomized complete block design. The parameters measured are the number of tillers, stem height, number of internodes, number of ears, ear length, stem and spike diameters and cycle duration. The results show on morphological parameters that MI 13/63 and MI 10/54 genotypes as an homogeneous population from M4 onwards. MI 12/72 can be classified into two different subgroups according to ear length. MI 02/82, on the other hand, shows a high degree of variability at M4. These results will contribute to the selection of new varieties adapted to the requirements of rural producers to improve pearl millet productivity in Niger.